A novel method for determining peroxisomal fatty acid β‐oxidation. Issue 5 (20th June 2016) - Morita, Masashi; Matsumoto, Shun; Okazaki, Airi; Tomita, Kaito; Watanabe, Shiro; Kawaguchi, Kosuke; Minato, Daishiro; Matsuya, Yuji; Shimozawa, Nobuyuki; Imanaka, Tsuneo
Abstract: The purpose of this study is to establish an assay method to screen for chemical compounds that stimulate peroxisomal fatty acid β‐oxidation activity in X‐linked adrenoleukodystropy (X‐ALD) fibroblasts. In this investigation, we used 12‐(1‐pyrene)dodecanoic acid (pyrene‐C12:0), a fluorescent fatty acid analog, as a substrate for fatty acid β‐oxidation. When human skin fibroblasts were incubated with pyrene‐C12:0, β‐oxidation products such as pyrene‐C10:0 and pyrene‐C8:0 were generated time‐dependently. These β‐oxidation products were scarcely detected in the fibroblasts from patients with Zellweger syndrome, a peroxisomal biogenesis disorder. In contrast, in fibroblasts with mitochondrial carnitine‐acylcarnitine translocase deficiency, the β‐oxidation products were detected at a level similar to control fibroblasts. These results indicate that the β‐oxidation of pyrene‐C12:0 takes place in peroxisomes, but not mitochondria, so pyrene‐C12:0 is useful for measuring peroxisomal fatty acid β‐oxidation activity. In X‐ALD fibroblasts, the β‐oxidation activity for pyrene‐C12:0 was approximately 40 % of control fibroblasts, which is consistent with previous results using [1‐ 14 C]lignoceric acid as the substrate. The present study provides a convenient procedure for screening chemical compounds that stimulate the peroxisomal fatty acid β‐oxidation in X‐ALD fibroblasts.